Application of Single Exponential Smoothing for Sales Forecasting: A Data-Driven Approach to Demand Management - Robbi Djefri Lakatua; Jondry Adrin Hetharie; Kiz Inalessy Manuhutu (Univiversitas Dr. Djar Wattiheluw, 2025)
Forecasting is a method used to predict future values based on historical data. This study aims to analyze and apply the Single Exponential Smoothing (SES) method to forecast the sales volume at Cafe Sibu-Sibu 01 for the upcoming period. The data used in this research consist of monthly sales records from January 2022 to December 2023. The forecasting results are then evaluated for accuracy using Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percentage Error (MAPE). The findings indicate that the sales volume for January 2024 is projected to increase to approximately IDR 68,882,000. With a smoothing constant of 0.1, the obtained values are MAD = 8,210.9, MSE = 114,138,110, and MAPE = 11.4%. Based on these results, it is concluded that the Single Exponential Smoothing method can be effectively used to forecast sales volume at Cafe Sibu-Sibu 01.